TENDENCIES OF HIGHER PEDAGOGICAL DEVELOPMENT SCHOOLS OF UKRAINE IN THE LIGHT OF REQUIREMENTS THE BOLOGNA PROCESS (Pedagogy of Higher and Secondary Education, 2022)
The article contains the analysis of works of scientists dedicated to the development of higher pedagogical education in Ukraine from 1985-to 2003. The main tendencies, directions, achievements, and problems of this development are characterized.